PELATIHAN PEMBUATAN MATERI PRESENTASI INTERAKTIF UNTUK KELOMPOK KERJA GURU JAKARTA BARAT - Carlene Lim; Viny Christanti Mawardi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
The COVID-19 pandemic has lasted 2 years which has resulted in the rapid development of the world of information technology, especially in the world of education. Online and hybrid learning have been carried out, especially in primary school education. In 2021, the design of the tutoring application concept has been carried out to be used by the English Teacher Working Group (Kelompok Kerja Guru-KKG) at the elementary level. This application can be used if teachers can arrange material in digital form in the form of subject matter, quiz questions, puzzles, and audio-video material. Teachers as pioneers of educational success must continue to be able to innovate in preparing interesting and interactive presentation materials to reduce the level of saturation of elementary school students. Therefore, training in making interactive materials for the English KKG is very necessary. The method of implementing this activity is to provide 2 online and hybrid trainings. The training was conducted for 2 types of software commonly used to create presentation materials, namely Microsoft PowerPoint and Google Slides. Based on the evaluation form filled out by participants from the English KKG, the result of this activity was that 100% of the participants understood how to access PowerPoint from Office 365 and understood how to use Morph transitions and animation features. 100% of participants can also know how to access Google Slides and know how to make classes and assignments using Google Classroom.